Analisis Dinamika Volatilitas Indeks Harga Saham Gabungan (IHSG): Aplikasi Model Threshold GARCH - Ahmad Albar Tanjung; Muliyani; Dian Purnama Sari (Journal of Trends Economics and Accounting Research, 2025)
The Jakarta Composite Index (JCI) is an important indicator for assessing the condition of the Indonesian economy, especially amidst the current trade war between the United States and China. The problem is that many stock movements are asymmetric, with differences in volatility occurring during increases and decreases in stock returns. This study aims to determine the best model and analyze the volatility dynamics of the Jakarta Composite Index (JCI) using the Threshold GARCH model. The data used are secondary stock return data from https://id.investing.com/indices/idx-composite-historical-data. The data range is from January 2019 to April 2025, with a daily period, with 1,523 observations. The results of this study indicate that the best model for observing asymmetric volatility is TGARCH(1,1), as it meets the non-negativity constraint assumption. The Composite Stock Price Index (IHSG) has volatility with an asymmetric effect with a gamma value () = 0.01336 and is significant, meaning that negative shocks in the form of negative news, such as the trade war crisis and Covid-19, cause greater volatility than positive shocks.